Analysis of the Utilization of Physics Laboratories in State Senior High Schools in Luwu Regency - Nur Ilmi Shaqinah; Helmi Helmi; Bunga Dara Amin (Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze the utilization of the physics laboratory and identify the factors causing the non-optimal use of the physics laboratory in state senior high schools throughout Luwu regency. This research is a survey research with a quantitative approach. Data analysis used descriptive analysis in the form of percentages involving three high schools in Luwu district, namely SMAN 12 Luwu, SMAN 7 Luwu, and SMAN 1 Luwu. The total number of student respondents was 223 students with 103 students at SMAN 12 Luwu, 56 students at SMAN 7 Luwu, and 64 students at SMAN 1 Luwu. In addition, there were 2 teachers in each of the three schools who were used as respondents. Data were collected by observation, questionnaires, and interviews. The results showed that the use of physics laboratories in state senior high schools throughout Luwu regency for practicum activity planning indicators was in a good category, teacher readiness indicators were in a good category, indicators for the implementation of practical activities were in a good category, and indicators for the availability of practicum tools were in the less category. This study concludes that not all indicators of the use of physics laboratories in state senior high schools throughout Luwu Regency are in a good category. The factor causing the non-optimal use of the physics laboratory is the incomplete availability of tools and practicum materials in schools.